The Influence of Brand Awareness and Promotion on Purchase Decisions of MACS Stationery Products in the West Java Region, Indonesia - Irfanudin, Ahmad Maulana; Andalusi, Ratih (Manunggal Halim Jaya, 2025)
This research aims to analyze the influence of brand awareness and promotion on purchasing decisions of MACS stationery products in West Java. The study uses a quantitative approach with a descriptive and verification method. Data were collected through questionnaires distributed to a population consisting of MACS consumers in West Java. Using non-probability sampling with purposive sampling technique, a total of 100 respondents were selected as the sample. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software version 26. The results showed that both brand awareness and promotion have a positive and significant influence on consumer purchasing decisions. The coefficient of determination (R²) indicates that 39.3% of the variation in purchasing decisions is explained by the two independent variables, while the remaining 60.7% is influenced by other factors not examined in this study. The findings highlight the importance of strengthening brand awareness and implementing effective promotional strategies to increase consumer purchasing behavior